Sovietinio laikotarpio architektūros konkursų raidos apžvalga - Linartas, Darius (Journal of Architecture and Urbanism, 2009)
Review of architectural competitions of the soviet period in Lithuania The paper deals with the main architectural competitions of the soviet period (1945–1990) in Lithuania. Referring to particular examples, efforts are made to identify development regularities of competitions at different stages of the soviet period, find out a relationship with the general architectural situation, discuss changes, to make a comparison with competitions of other historical epochs as well as to define their influence on the architecture and architects in Lithuania of that time. Peculiarities of competitions related to urbanistic projects, buildings and monuments representing both the early and “mature” socialism are introduced. Without attempting to list and examine in detail each creative competition of this era, efforts are made to perceive the essential principles of the very competition system of the soviet period. Problematicity related to “dead” projects, non-transparency of competitions and disregard of copyright typical to the Soviet times are discussed. Article in Lithuanian. Santrauka. Straipsnyje aptariami svarbesni sovietinio periodo (1945–1990 m.) architektūros konkursai Lietuvoje. Peržvelgiami ankstyvojo ir vėlyvojo socializmo urbanistinių, pastatų, monumentų konkursų ypatumai. Apra[sbreve]omai epochai būdinga „mirusių“ projektų, konkursų nerezultatyvumo ir neskaidrumo problematika. Remiantis esmingesniais konkrečių kūrybinių varžybų pavyzdžiais bandoma atsekti konkursų raidos dėsningumus įvairiais laikotarpio etapais, rasti santykį su bendra laikmečio geopolitine situacija, aptarti pokyčius, palyginti su kitų istorinių periodų konkursais, nustatyti galimą reik[sbreve]mę to meto Lietuvos architektūros vystymuisi ir architektų tobulėjimui. Reikšminiai žodžiai: architektūros konkursas, sovietiniai metai, „miręs“ projektas, įgyvendinimas, autorystė. First Published online: 21 May 2013